Analisis Tingkat Konservatisme Akuntansi (Conditional) Selama Pandemi Covid-19 - Intan Wahyu Zulhijmi; Nurzi Sebrina (Universitas Negeri Padang, 2023)
This study aims to analyze differences in accounting conservatism before and during the Covid-19 pandemic. This research is a comparative study that aims to compare one or more variables in two or more different samples or more than one. This study uses secondary data obtained from the website www.idx.co.id. The population in this study was listed on the Indonesia Stock Exchange (IDX) during 2018 - 2021. This study used a purposive sampling technique and obtained 412 companies. The data in this study were tested using Kolmogorov Smirnov normality and hypothesis testing using the Wilcoxon Signed Rank Test for conservatism proxy by used earning/stock return relations measure method. The results of this study indicate that there is no difference in conditional conservatism before and during the Covid-19 pandemic.